2021
DOI: 10.3390/agronomy11061202
|View full text |Cite
|
Sign up to set email alerts
|

Rapid Detection and Counting of Wheat Ears in the Field Using YOLOv4 with Attention Module

Abstract: The detection and counting of wheat ears are very important for crop field management, yield estimation, and phenotypic analysis. Previous studies have shown that most methods for detecting wheat ears were based on shallow features such as color and texture extracted by machine learning methods, which have obtained good results. However, due to the lack of robustness of these features, it was difficult for the above-mentioned methods to meet the detection and counting of wheat ears in natural scenes. Other stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
45
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 83 publications
(46 citation statements)
references
References 34 publications
0
45
0
1
Order By: Relevance
“…Relevant studies are successful in applying deep learning models in wheat ear detection. Based on the image processing and deep learning technology, the EfficientDet algorithm ( Tan, Pang & Le, 2020 ) was used to detect the wheat ear image by Cao et al (2020) , the final accuracy rate reached 92.92% and the test time of the single sheet was 0.2 s. An improved YOLOv4 with CBAM (convolutional block attention module) ( Woo et al, 2018 ) including spatial and channel attention model was proposed by Yang et al (2021) . This strategy could enhance the feature extraction capabilities of the network by adding receptive field modules.…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…Relevant studies are successful in applying deep learning models in wheat ear detection. Based on the image processing and deep learning technology, the EfficientDet algorithm ( Tan, Pang & Le, 2020 ) was used to detect the wheat ear image by Cao et al (2020) , the final accuracy rate reached 92.92% and the test time of the single sheet was 0.2 s. An improved YOLOv4 with CBAM (convolutional block attention module) ( Woo et al, 2018 ) including spatial and channel attention model was proposed by Yang et al (2021) . This strategy could enhance the feature extraction capabilities of the network by adding receptive field modules.…”
Section: Related Workmentioning
confidence: 99%
“… Xu et al (2020) used the K-means clustering method for automatic segmentation of wheat ear images and sent the segmented image tags to the convolutional neural network model for training and testing. Although much progress ( Cao et al, 2020 ; Yang et al, 2021 ; Xu et al, 2020 ) has been made, there are still problems such as low efficiency, insufficient robustness, and poor performance. Simultaneously, the above-mentioned deep learning-based detection methods often need to sacrifice accuracy to ensure the inference speed of the detector because of the limitation of hardware in practice.…”
Section: Related Workmentioning
confidence: 99%
“…In our opinion, such adaptive systems have a serious drawback, they cannot be customized to the individual characteristics of each root crop. In digital agriculture [10,11], computer vision systems are used to quickly detect and count plants [12][13][14][15], to determine their ripeness and diseases [16][17][18][19][20], as part of systems to protect against weeds and pests [21,22], to determine the position of cattle [23]. In recent years publications have shown that the problem of identifying diseased or mechanically damaged fetuses on transportation systems such as conveyor belts, drums, turbines and etc.…”
Section: Introductionmentioning
confidence: 99%
“… Sadeghi-Tehran et al (2019) constructed wheat feature models and fed the models into convolutional neural networks to achieve semantic segmentation and automatic counting of wheat. In addition, TasselNetv2 ( Xiong et al, 2019 ), mobileNetV2 ( Khaki et al, 2021 ), YOLOV4 ( Yang et al, 2021 ), EfficientDet ( Wang et al, 2021 ), LPNet ( Misra et al, 2020 ), and other deep-learning networks have shown advantages in wheat counting.…”
Section: Introductionmentioning
confidence: 99%